Resepsi Sinkronis Alumni Mahasiswa FIB UNS terhadap Keindahan Puisi Berbahasa Indonesia dalam Lagu A Rose In The Wind Karya Anggun - Irwanto Irwanto (Program Studi Sastra Indonesia, Fakultas Ilmu Budaya, Universitas Diponegoro, 2019)
This research aimed on the responses from almuni of the UNS Faculty of Humanities to Indonesian poetry in Anggun C Sasmi's international song A Rose in The Wind. The agreement that used in this study is the synchronous acceptance of literary work. The researcher chosed and interviewed 5 respondents from alumni of UNS Faculty of Humanities. The result of interview resulting a data that used as material of research. The researcher found similarities and responses on the poetry tittle. There also different reason, which are some interpretation of the responded that related to feelings of regret, apologies, and nationalism. One interesting thing in this research is the shift in the meaning of natinoalism towards Indonesia. As it related to nationalism, it is not only given by the